Meras Gandrung Tradition as a Cultural Strategy for the Regeneration of Gandrung Dancers in Banyuwangi: Tradisi Meras Gandrung Sebagai Strategi Budaya Untuk Regenerasi Penari Gandrung Di Banyuwangi - Mahfud; Mutiara Cahya Ayuning Tyas; I Kadek Yudiana (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Gandrung is one of the works of art that became a means to express the inner state of Banyuwangi people during the Dutch era, Gandrung became an important icon. This is why the regeneration of Gandrung dancers is very important, requiring a strategy to attract the sympathy of the younger generation regarding the Meras Gandrung tradition. The purpose of this research is to be an important contribution to the development of effective cultural strategies, bridging the gap between tradition and the times, and ensuring the continuity of a cultural heritage that is very valuable to the people of Banyuwangi. The form of this research is descriptive qualitative. The theory used is the theory of cultural inheritance by Edward T. Hall. Data collection techniques using interviews, observations, and document studies. The results of the research show that the existing strategy is an important movement so that students or even the general public know that to become a Gandrung must go through the Meras Gandrung Tradition, the infrastructure created by the government is an important forum for Gandrung maestros and fairies to convey the meaning of Gandrung, besides that the Meras Gandrung Performance is an important strategy because it involves young Banyuwangi dancer students to know the process and meaning of Gandrung. This can be studied using the theory of cultural inheritance according to Edward T. Hall, in his theory of cultural inheritance, emphasizes the importance of the cultural level dimension. He understands that the values, norms and communication patterns of a culture can be passed on and maintained through generations. His concept of cultural level dimensions includes differences in such things as perceptions of time, interpersonal space, and ways of communicating, all of which contribute to how culture is passed on and continues in a society.